Khap Panchayat: Retrieving ‘Honour’ through Violence - Yamin Khan (International Journal of Engineering and Management Research, 2021)
As the custodians of honour, Khap Panchayats are self-proclaimed tribunals with full validity and authority among the segments of their caste. These Panchayats are not real courts and do not have a constitutional basis. Under this unconstitutional system, all people of a village huddle around a Chabutara in order to make rapid, unilateral, and incontestable decisions on a variety of problems such as social transgression, marriage, offences, property rights, or situations endangering the village's tranquillity. It is concerning to notice that, in an era where individuals communicate via 3G technology, Indian civilization has regressed to the Dark Age. In today's culture, when legal standards and constitutional authority rule society, organisations like the Khap Panchayat obstruct progress and good government. The residents of the particular territory or community in which 'Khap' exists praise the dictates of Khap Panchayat; this is the most significant hurdle to Khap Panchayat's elimination. This study attempts to answer the question, "Why do Khaps still exist in India?" What is Khap's source of strength? It provides a thorough examination of the problem and attempts to propose a solution.